Sistem Informasi Akuntansi Penjualan Kredit Meningkatkan Pengendalian Intern Pada Dealer Mitsubishi Candi Sidoarjo - Rohmah Putri Ariutami; L. Tri Lestari; Masyhad Masyhad (Universitas Bhayangkara Surabaya, 2024)
Indonesia is experiencing a rapid surge in technological advancement. However, these advancements also expand the influence of the business environment, causing competition to intensify. A robust accounting information system is essential for effectively managing sales competition. A company's internal controls have a significant impact on its business continuity; without robust internal controls, credit sales may fail. This is a particular car dealership that employs a sales accounting system, which prompted the researcher to investigate the system. The research employs a descriptive qualitative data collection technique, which has yielded the conclusion that the current sales credit accounting system utilized by the dealer is suboptimal. Consequently, enhancements are necessary to diminish the incidence of bad debts in the billing department.